Evaluasi Dan Refleksi Pendidikan Agama Islam Pada Siswa SMK Sultan Syarif Kasim Kecamatan Kandis - Supriadi, Supriadi; Nasution, Juni Eprida (EL-EMIR Institute, 2025)
This study aims to evaluate and reflect on the implementation of Islamic Religious Education (PAI) among students at SMK Sultan Syarif Kasim, Kandis District. Islamic Religious Education plays an important role in shaping students’ character, morals, and spirituality, particularly at the Vocational High School (SMK) level, which prepares students to enter the workforce.This research employed a descriptive qualitative approach, with data collected through observation, interviews, and questionnaires administered to students and Islamic Religious Education teachers. The findings indicate that the implementation of PAI learning has been carried out in accordance with the curriculum. However, several challenges remain, including limited instructional time, low active participation among some students, and the influence of the social environment and digital technology. The evaluation results show that 72% of students achieved scores above the Minimum Competency Criteria (KKM), while 28% still require further guidance and improvement. The reflection on the learning process emphasizes the importance of innovating teaching methods that are more contextual, integrative, and character-based, so that Islamic values are not only understood theoretically but also applied in daily life. Furthermore, collaboration among teachers, parents, and the school administration needs to be strengthened to create a conducive religious environment. Therefore, this evaluation and reflection are expected to serve as a foundation for continuous improvement in enhancing the quality of Islamic Religious Education at the school.